2021
DOI: 10.1371/journal.pone.0257778
|View full text |Cite
|
Sign up to set email alerts
|

Does exogenous female sex hormone administration affect the rate of tooth movement and root resorption? A systematic review of animal studies

Abstract: Background The long-term use of contraceptive methods that contain estrogens, progestogens or combinations of the above among women aged 15 to 49 years is extensive. Both estrogens and progestogens affect bone metabolism. Objective To systematically investigate and appraise the quality of the available evidence from animal studies regarding the impact of exogenous administration of female sex hormones on the rate of orthodontic tooth movement and root resorption. Search methods Search without restriction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Dental movements are expected to be greater in younger patients and in women due to their lower bone densities [ 26 ]. Nevertheless, in our study no significant relationship between age and dental or skeletal changes was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Dental movements are expected to be greater in younger patients and in women due to their lower bone densities [ 26 ]. Nevertheless, in our study no significant relationship between age and dental or skeletal changes was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Cementoblastic activities and the amount of new cementum formation are lower in ovariectomized rats, thus affecting the activation of extracellular signal-regulated kinase-1/2 pathway. Given the similarity between cementoblasts and osteoblasts, it is unsurprising that some scholars manage to reduce EARR by locally injecting a variety of bone forming associated hormones in animals (e.g., estrogen, thyroxine, prostaglandin E2, and parathyroid hormone) [129][130][131][132]. However, the underlying mechanisms and the effects of local application of hormones BioMed Research International on immune status remain unclear, and it is necessary to conduct further investigations.…”
Section: External Root Resorptionmentioning
confidence: 99%